High‐efficiency organic light‐emitting diodes based on the gradient doping and nonlinear cross‐fading doping in transporting layers. Issue 1 (16th April 2014) - Wang, Jing; Huang, Saijun; Liu, Jun; Wu, Xinkai; Shi, Xindong; Chen, Chaoping; Ye, Zhicheng; Lu, Jiangang; Su, Yikai; He, Gufeng
Abstract We have demonstrated that carrier injection and transporting can be fine‐tuned via gradient p‐doping and n‐doping in organic light‐emitting diodes. The doping profile of gradient doping in transporting layer is ultrahigh at the electrode side, declining gradually with the depth into the device until the emission layer. This not only ensures perfect charge injection from electrode to organic transporting layer but also proves an efficient charge transport for light emission. It is proposed that low doping ratio close to the emission layer may avoid possible quenching of excitons by the diffusion of dopant as well. A device based on gradient doping has been proved to obtain better carrier injection and achieve higher external quantum efficiency. To get smoother charge injection and transporting, and simplify the fabrication process, we have developed a nonlinear cross‐fading doping in transporting layer, which has been demonstrated to further enhance the current density characteristics.